Disability, Subversion and the “Creative Fidelity” in the Film Adaptation of Suraj Ka Satvan Ghoda (1992) (KEMANUSIAAN The Asian Journal of Humanities, 2026)
The article looks at Shyam Benegal’s 1992 film adaptation of Dharamveer Bharati’s novel, Suraj Ka Satvan Ghoda (The Sun’s Seventh Horse), published in 1952, through the analytical lenses of disability, gender and the theoretical construct of “creative fidelity” in adaptation. By juxtaposing the cinematic text with its literary precursor, this study interrogates Benegal’s hermeneutic reconstruction of marginalised identities, particularly those of women and individuals with disabilities. Situated in an examination of their respective sociopolitical contexts, the analysis scrutinises the extent to which Benegal’s adaptation destabilises or consolidates dominant cultural narratives surrounding disability, gender and class/caste. The findings demonstrate a complex interlacing of subversion and compliance that characterises the adaptation’s reconstruction of different themes, offering a comprehensive critique of its sociopolitical positioning. This study contributes to the broader discourse on representational politics in Indian cinema and contends that the adaptation is a liminal space where hegemonic paradigms are both interrogated and reaffirmed.